THE IMPLEMENTATION OF QUIZ TEAM TYPE ACTIVE LEARNING STRATEGY TO INCREASE THE UNDERSTANDING ON MOVEMENT SYSTEM CONCEPT AT JUNIOR HIGH SCHOOL - Wahyuni, Hiatun Sri; Agustini, Rudiana; Prastowo, Tjipto (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
This study was conducted to increase the understanding on movement system concept at Junior High School.This study belongs to pre-experimental using One Group Pretest and Posttest Design. Subjects of the research were 32 students. Analysis of research data is carried out descriptive quantitatively. Result of this study shows that: (1) lesson plan gets average score of 3.72 which is categorized as excellent; (2) Normalized Gain Score  is 0.71; and (3) students response positively; 98,74% of students state they are pleased with this teaching model, 96,88% state it is new for them, 98,75% state it is easyto do, 98,13% state their agreement, and 91% request the application of this model on the following lessons; and (4) the highest learning activity is reading teaching material, of 22,85% students. As a conclusion from this research is that quiz team model of teaching is applicable to increase the understanding on movement system concept at Junior High School.